Respuesta :

Values of the composite function:

[tex](g\cdot f)(-1)=6[/tex]

[tex](g\cdot f)(0)=7[/tex]

[tex](f\cdot g)(-1)=3[/tex]

[tex](f\cdot g)(4)=2[/tex]

Step-by-step explanation:

Given two functions f(x) and g(x), their composite function is given by

[tex](f\cdot g)(x) = f(g(x))[/tex]

Which means using the output value of g(x) as input for f(x).

Let's start by computing

[tex](g\cdot f)(-1)[/tex]

First, we compute the value of f(-1), which is (from the graph)

f(-1) = 1

Now we use this value as input into g(x); we notice that at x = 1, the value of g(x) is 6, therefore:

[tex](g\cdot f)(-1)=6[/tex]

Now we evaluate

[tex](g\cdot f)(0)[/tex]

First, we compute the value of f(0), which is (from the graph)

f(0) = 0

Now we use this value as input into g(x); at x = 0, the value of g(x) is 7, therefore:

[tex](g\cdot f)(0)=7[/tex]

Now we evaluate

[tex](f\cdot g)(-1)[/tex]

First, we compute the value of g(-1), which is (from the graph)

g(-1) = 5

Now we use this value as input into f(x); at x = 5, the value of f(x) is 3, therefore:

[tex](f\cdot g)(-1)=3[/tex]

Finally we evaluate

[tex](f\cdot g)(4)[/tex]

First, we compute the value of g(4), which is (from the graph)

g(4) = 4

Now we use this value as input into f(x); at x = 4, the value of f(x) is 2, therefore:

[tex](f\cdot g)(4)=2[/tex]

Learn more about composite functions:

brainly.com/question/2723982

brainly.com/question/2456302

brainly.com/question/1949601

brainly.com/question/1900154

#LearnwithBrainly